Competency and Leadership Towards Work Commitment Through Loyalty in the Detachment of Indonesian Navy Force Headquarters - Wibisono, Chablullah; Susanto, Eko Agus; Khaddafi, Muammar; Indrawan, Mohamad Gita (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
The Indonesian Navy is responsible for guarding Indonesia's territorial waters and protecting the country from threats coming from the sea. A strong work commitment ensures TNI AL personnel are always ready, on guard, and highly dedicated. This research examines the Navy members' work commitment, influenced by Competence and Leadership as an intermediary with the Navy members' Loyalty. This research method is quantitative research that utilizes primary data. Based on sample calculations using the Slovin formula, 136 respondents were obtained who were members of the Indonesian Navy who served in the Headquarters Detachment. The research results show that Competency and Leadership do not directly affect Work Commitment but rather affect Loyalty. Furthermore, Loyalty is proven to mediate Competence in Work Commitment, mediating the relationship between Leadership and Work Commitment. The results of this research can be used as material to highlight the performance of the TNI Navy and as a reference for determining TNI Navy human resource policies.